Poor Background or Low Returns? Why Immigrant Students in Germany Perform so Poorly in PISA - Andreas Ammermüller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Student performance of Germans and immigrants differed greatly in the 2000 PISA study. This paper analyses why the two groups of students performed so differently by estimating educational production functions, using an extension study with imputed data. The difference in the test scores is assigned to different effects, using a Juhn-Murphy-Pierce decomposition method. The analysis shows that German students have on average more favorable characteristics and experience slightly higher returns to these characteristics in terms of test scores than immigrant students. The later enrolment of immigrant students and preferences of parents as reflected by the number of books and language spoken at home are more important than parents? education or the family setting for explaining the test score gap. Overall, the variation in test scores can be explained better by the observable characteristics for immigrant than for German students.
Keywords: H52; I21; 330; Educational production; PISA-E; decomposition; immigration; Schüler; Bildungsverhalten; Bildungschancen; Migranten; Deutschland